Peningkatan Kemampuan Guru dalam Mengefektifkan Pembelajaran melalui Supervisi Kelas pada SD Negeri 45 Ampenan - Muttaqin, Zainul (Lembaga Yasin AlSys, 2023)
The purpose of this school action research is to find out the increase in the teacher's ability to make learning effective through Class Supervision at SD Negeri 45 Ampenan for the 2022/2023 school year. This research is classified as School Action Research involving 8 teachers who need to improve their ability to effectively manage their learning. The research was conducted in two cycles and each cycle consisted of four stages: planning, implementing, observing and reflecting. The performance indicators set are: if there is an increase in the ability to effectively manage learning. The results of the study show that there is an increase in the teacher's ability to make learning effective through classroom supervision. It can be concluded as follows: (1) The application of learning models through class supervision by the principal has proven successful in increasing the ability of SD Negeri 45 Ampenan teachers in managing the learning process. (2) By increasing the ability of SD Negeri 45 Ampenan teachers in managing the learning process, in addition to making the students' learning process more meaningful, their learning outcomes have also increased. (3) The application of academic supervision of class visits has a positive impact because it can assist the teacher's duties in planning and implementing learning in the framework of increasing professionalism.